FOODBORNE OUTBREAKS AND FARM STRUCTURE: AN EXAMINATION OF VEGETABLE AND MELON FARMING - Ioana (Julia) Marasteanu; Travis Minor (International Journal of Food and Agricultural Economics, 2017)
This paper examines the association of foodborne outbreaks with farm and labor density. Using a novel data set, comprised of state level agricultural statistics from the US Census Bureau combined with foodborne outbreak information compiled by the Centers for Disease Control and Prevention from 2004 to 2014, we find that, within the vegetable and melon industry, raw outbreaks do not appear to be significantly correlated with a decrease in farm numbers. However, taking into account the severity of an outbreak suggests a negative long-term correlation between farming establishments in an affected state. Labor also appears to be correlated with outbreaks, positively in the near-term but negatively overall. Finally, spatial results suggest that nearby markets may be impacted by vegetable and melon outbreaks, and that states tend to be surrounded by neighbors with dissimilar outcomes.